Financing Funding Strategy Professionalism of Indonesian Migrant Workers As the Current Account Deficit Solution - Reny Fitriana Kaban; Selamet Riyadi (Universitas Gorontalo, 2020)
This research aims to describe the phenomenon of the current account deficit problem in Indonesia especially service balance for the last ten years due to a low number of migrant workers in the formal sector, despite the increase of remittance numbers. The research method is descriptive exploratory, which describes and analyses accurate data such as BI annual reports, data from BP2MI (previously BNP2TKI), and data from related institutions also some supportive kinds of literature. The Result shows the professionalism of Indonesian Migrant Workers has proven in making a significant contribution to increase the remittance and solve the deficit of the current account. Authors recommend the Synergy and Coordination of Funding Financing (SCFF) strategy concept which involves various concerning sectors as a solution for the current account deficit.